Collage Media to Develop Fine Motor Skills in Early Childhood - Nur Arifah Hanafiah; Sabil Mokodenseho; Ratna Ayu Pawestri Kusuma Dewi; Achmad Zahruddin; Hersiyati Palayukan (Bulletin of Early Childhood, 2023)
Fine motor is one aspect of motor development that must be developed in early childhood education. Fine motor has a vital role in child development because fine motor is the child's ability to show and master beautiful muscle movements in coordination, agility, and dexterity in using hands and fingers. To develop fine motor skills, a teacher must be able to sort and choose the suitable media to build it optimally and as expected. This study used qualitative research methodology. The research subjects were 20 students and two teachers from RA Lampung Timur, while the research object was the development of children's fine motor skills. The approach used is qualitative with descriptive research methods; the author describes or describes the findings systematically and accurately using a series of words or sentences so they can be understood. The data collection techniques used are observation, interviews, and documentation. The results showed that applying collage media to develop children's fine motor skills could be successful. Keywords: collage media, fine motor, early childhood